REDESAIN TAMAN AGROWISATA REKADENA DI KABUPATEN KUBU RAYA - Caroline, Ivon; Affrilyno, Affrilyno; Muazir, Syaiful (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Agrotourism is an effort to boost the economy by utilizing the agricultural sector as its main focus. Agrotourism is a type of activity that attracts tourists by offering farming experiences and involving local residents in the planning and management processes of the area. One of the agrotourism destinations in Kubu Raya Regency is Rekadena Agrotourism located on Jeruju Besar Street, Sungai Kakap District, Kubu Raya Regency, West Kalimantan. The Rekadena Agrotourism Park area has several facilities such as vehicle parking areas, outbound activities, camping grounds, fishing ponds, restaurants, halls, health clinics, and prayer rooms. However, the Rekadena Agrotourism Park has not yet met several standards of facilities and infrastructure in tourism. The objective of this design is to redesign the Rekadena Agrotourism Park in accordance with the standards of facilities and infrastructure and to provide job opportunities for the local community in Kubu Raya Regency. The concept used in this design emphasizes the objectives and functions of the buildings or areas themselves. The method used in this design refers to Richard Whitaker's design method, which includes the stages of introducing Rekadena Agrotourism Park, identifying issues for redesigning Rekadena Agrotourism Park, collecting theories related to agrotourism parks, analyzing design standards, developing concepts, completing the design, and creating pre-design drawings and technical drawings. The result of this design is the redesign of Rekadena Agrotourism Park in Kubu Raya Regency.